STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA KARYAWAN DI UMKM ANGKRINGAN IKI TULUNGAGUNG - Azis, Nova Farizal; Fauji, Diah Ayu Septi; Leksono, Poniran Yudho (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to find out how the HRM strategy in improving employee performance. In this study the authors used a type of qualitative research with a descriptive case study approach. Data collection techniques using interviews, observation, and documentation. Obtaining data from primary sources, namely the results of interviews with the Owner, Manager, and Captain of the Angkringan Iki Field. To check the validity of the data the author uses data source triangulation. Based on the research results, it can be concluded that Angkringan Iki Tulungagung is a fairly good business in implementing the HRM system. Among them are the signature of the employment contract with a matrait in the work contract agreement, briefing, evaluation, the existence of an SP (warning letter) system, training system, division of task structures and changes to the distribution of task structures every month, implementation of a family management system for employees, compensation incentives and facilities, gatherings held once every year, termination of employment due to expiration of the work contract and resignation due to the employee himself.